Histopathological changes of the liver induced by sodium nitrite (NaNO2) And Extract Of Sweet Flag Rhizome (Acorus calamus L.) Of Rat (Rattus norvegicus L) - Hoirun Nisa, Novita; Tambunan , Efrida Prima Sari; Syukriah (LenteraBio : Berkala Ilmiah Biologi, 2023)
Sodium nitrite is a colorant in processed meat and is usually consumed by the public at large. Excessive consumption of sodium nitrite can cause liver cell damage. Jeringau (Acorus calamus L.) is an herbal plant that contains flavonoids. The activity of flavonoids is thought to be used as an anti-inflammatory, analgesic and antioxidant. research aims to determine the effect of sodium nitrite (NaNO2) and extract of sweet flag rhizome (Acorus calamus L.) on morphology and Histopathological changes of the liver for rat (Rattus norvegicus L.). This study used a completely randomized design (CRD) consisting of 5 treatments (P0: 0.5% CMC Na, P1: sodium nitrite and 0.5% CMC Na, P2: 250 mg/kg BW, P3: 500 mg dose. /kg BW, P4: dose 750 mg/kg BW). The treatment was carried out for 40 days. Scoring method usingmodel Manja Roegnik's Histopathology and histomorphometry on liver cell damage were analyzed by one-way ANOVA and Duncan's test at a significant level of 0.05 on SPSS 28. The results showed that the administration of a dose of 250 mg/kg BW and 500 mg/kg BW could significantly improve liver histopathological damage. (p?0.05) compared to the control group. The conclusion of this study is that jeringau rhizome extract can reduce the level of damage to hydropic degeneration and necrosis of the liver.